Economic crisis in Greece: The invisible enemy of blood donation or not?. (December 2022) - Fortis, Sotirios P.; Kriebardis, Anastasios G.; Georgatzakou, Hara T.; Lyrakos, George; Alexiou, Panagiotis; Antoniou, Charalampos; Papadopoulos, George; Stamoulis, Konstantinos E.; Valsami, Serena
Abstract: Introduction: Volunteering presupposes having free time and refers to the provision of services without the motivation of material reward, for the benefit of society. In this study, we aimed to provide insight into the impact of economic crisis on blood donors and their motivation to donate blood during that period. Study Design and Methods: We asked blood donors about their blood donation activity and motivation to donate using a standardized, anonymous questionnaire (n = 3000). Descriptive analysis was performed for the consideration of donor turnout during this economic period. The results were analyzed using the χ 2 test and Spearman's correlation coefficient. Results: Regarding gender, 68.2% were males, while 31.8% were females. Most blood donors donated voluntarily (75.8%) and only 24.2% were replacement or family blood donors. The economic crisis has affected the inhabitants of Athens more than the inhabitants of the province ( χ 2 = 9.910, p = 0.007). The influence of economic crisis on the regular blood donors' quality of life was greater than the non-regular donors ( χ 2 = 16.227, p < 0.001). According to our results, the economic crisis reduced the quality of life, but it did not affect the frequency of blood donations in a percentage of 87, 3%. Not any significant difference was found between employment status, economic crisis and blood donation. Conclusion: Although the economic crisis has affected the lives of blood donors, it does not seem to affect the frequency of blood donation. We suggest that blood collection services should consider specialist campaigns that focus on the altruistic motivation of donors during an economic crisis.